Tourism Economic Development Strategy Based on Local Culture in South Sulawesi - Dahlan, Mubarak (Research Agency for Humanity and Urban, 2024)
The development of the tourism economic sector in various countries in the world, including Indonesia, in recent years has become a trend issue, especially since it was realized that this sector has promising prospects in the future. This paper examines the importance of developing a culture-based tourism economic sector and the forms of its development strategy. This type of research is descriptive qualitative research with data collection techniques using written sources, namely books, articles, documents, and others. The results showed that South Sulawesi has a lot of enormous tourism potential so it is possible to develop the economic sector in this field. The development is not only required a precise strategy but also needs to be supported by the support of all parties both government and society in general. The fact shows that the development of the tourism sector in South Sulawesi so far is still constrained by many factors that require serious discussion and in-depth scientific studies, especially related to the optimization of development and utilization in the future.